Building bridges through learning as mediation parties' lived experiences: An interpretative phenomenological analysis. Issue 2 (17th November 2016) - Tallodi, Timea
Abstract : While abundant literature has been devoted to describe mediation, there is little research exploring how parties perceive and make sense of the process. This article reports two associated main themes from an innovative qualitative research project conducted to understand the lived experiences of parties to mediation using interpretative phenomenological analysis for the first time in the literature. The findings present (1) learning as the key experience of participants in mediation, a so far neglected angle of the process, and (2) the mediator's compassionate approach involving conveying ample understanding and sensitivity toward parties' needs and concerns as facilitating learning. Meanings and fresh concepts have been generated through sensitive and careful analysis of the cases, providing a rich portrait of the dynamics of learning, and the way learning bridges differences between the sides. Implications for mediators and research are outlined.